Availability of calcium in dairy and other human foods - I.J. Jeon (Kansas Agricultural Experiment Station Research Reports, 1986)
In 1985 the annual sales of dairy products on the average grew 3.3%, and is expected to grow 6.4% in 1986, according to the U.S. Department of Commerce. This positive growth was attributed in part to increased consumer awareness on the reported role of calcium in combating hypertension (high blood pressure) and osteoporosis (a brittle bone disease common in older women). A recent report suggested that many consumers are seeing the publicity that many cases of hypertension may be the result of too little calcium intake, not too much sodium. Consumers are also well aware that a calcium-deficient diet can result in the development of osteoporosis, a progressive loss of bone mass that leaves the skeleton fragile and vulnerable to fractures. The gradual loss in bone mass begins in the mid-30's but the damage is not apparent until at least 20 years later, when a significant amount of loss has occurred.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Calcium; Dairy products